Electronic processing and the principle of transparency in public procurement - Nekkache, Hamza (Journal of Human Sciences, 2022)
Transparency is considered an essential pillar for the smooth running of public procurement procedures. Rather, it is seen as one of the basic general principles of public procurement, as it provides a set of guarantees for the proper use of public money. On the one hand, it allows all players to access all the information on the mechanisms for disbursing public funds in the context of public contracts, on the other hand, it ensures the correct and fair treatment of all offers from entrepreneurs, thus reducing manifestations of corruption. To reinforce this principle, the electronic processing system for public contracts has been put in place, of which the Algerian legislator has provided the initial legal framework since 2010, and still lacks activation in the field, which requires the development of an integrated strategy that responds to international technical guidelines, and in the short term, that achieves efficiency in public procurement.